Quasi-exact solvable Dirac equation for the generalized Cornell potential plus a novel angle-dependent potential - Bouchefra, Djahida; Boudjedaa, Badredine (Journal of Innovative Applied Mathematics and Computational Sciences, 2024)
In this paper, we present the exact analytical solution of the Dirac equation with equal scalar and vector generalized Cornell potential plus a novel angle-dependent potential in the framework of quasi-exactly solvable problems. By applying the functional Bethe ansatz method, we derive the angular Dirac part solutions and by the biconfluent Heun differential equation, the radial Dirac part solutions are determined. The exact bound states and the corresponding energy eigenvalues are obtained. Overall, this paper is a general reference for many previous scientific researches because it includes many possibilities, both central and non-central, which in turn adds a new addition to theoretical physics as well as modern mathematics.